Desain Komik Berbasis Prolem Based Learning Bermuatan Konservasi Untuk Peningkatan Keterampilan Berpikir Kritis Dan Karakter Peduli Lingkungan - Nurlailatin Ni’mah; Tri Suminar; Sarwi Sarwi (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2021)
This study aims to: 1) describe and analyze teaching materials and learning models to improve critical thinking skills and environmental care characters carried out by teachers, 2) test the validity of the design of PBL-based comics teaching materials containing Conservation developed, 3) test the effectiveness of comics teaching materials PBL based on Conservation to improve critical thinking skills and environmental care character of students and 4) testing the effectiveness of PBL based comics teaching materials containing Conservation to improve students' environmental care character. The type of research used is research and development (Research and Development). The research development procedure consists of two main objectives, namely: (1) developing the product, and (2) testing the effectiveness of the product in achieving the goal. The results of research on teaching materials and learning models can improve the critical thinking skills and environmental care character of students by teachers. The design of comics teaching materials based on Problem Based Learning containing Conservation that was developed is a very feasible and valid teaching material. Teaching materials based on Problem Based Learning Comics containing Conservation to improve students' critical thinking skills are effective teaching materials. Comics teaching materials based on Problem Based Learning containing Conservation to improve students' environmental care character are effective teaching materials.